2007
DOI: 10.1109/tasc.2007.898247
|View full text |Cite
|
Sign up to set email alerts
|

Strong-Field Effects in the Rabi Oscillations of the Superconducting Phase Qubit

Abstract: Abstract-Rabi oscillations have been observed in many superconducting devices, and represent prototypical logic operations for quantum bits (qubits) in a quantum computer. We use a three-level multiphoton analysis to understand the behavior of the superconducting phase qubit (current-biased Josephson junction) at high microwave drive power. Analytical and numerical results for the ac Stark shift, single-photon Rabi frequency, and twophoton Rabi frequency are compared to measurements made on a dc SQUID phase qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…We refer to these additional changes in the qubit level splitting as the generalized Bloch-Siegert shift. This work differs from the previous studies on strong drive with superconducting or quantum dot qubits [5,6,[15][16][17][18][19][20][21][22][23][24][25][26], where the coupling of the drive to the qubit was linear.…”
mentioning
confidence: 63%
“…We refer to these additional changes in the qubit level splitting as the generalized Bloch-Siegert shift. This work differs from the previous studies on strong drive with superconducting or quantum dot qubits [5,6,[15][16][17][18][19][20][21][22][23][24][25][26], where the coupling of the drive to the qubit was linear.…”
mentioning
confidence: 63%
“…Its reduction is due to the dressed eigenstates of the system, and has also been measured experimentally [21,22,23,32] IV. TWO-MODE FLOQUET THEORY: OPTIMIZED RABI OSCILLATION…”
Section: Phase Qubit Hamiltonianmentioning
confidence: 74%
“…SINGLE-MODE FLOQUET THEORY: THREE-LEVEL RABI OSCILLATIONS For Rabi oscillations in the presence of strong driving, there are deviations from two-level behavior that can be analyzed using a three-level model. Previous studies [11,12,31,32], using the rotating wave approximation, have identified three main features. First, the coherent oscillations between the ground and first excited state are accompanied by oscillations to the second excited state.…”
Section: Phase Qubit Hamiltonianmentioning
confidence: 96%
See 2 more Smart Citations